Missional Discipleship in Post-Pandemic Korea: : The Case of Suwonsung Church - Lee, Bright Myeong-Seok (Ecclesial Futures, 2023)
The decline in social trust in the Korean Protestant church is a significant social issue that requires attention and action. Despite being more involved in community service than other religions, trust in the church has fallen, and it is essential to understand why. This paper will examine the previous dominant method of discipleship training, which may have contributed to this decline. By using a case study of a Korean church, the study will analyze the effectiveness of the discipleship training and its impact on social trust. Then I will reflect on how the Korean church should respond to today’s situation characterized by VUCA (volatility, uncertainty, complexity, ambiguity) and the pandemic. This paper will suggest a new approach called missional discipleship, which seeks to create a more engaging and inclusive environment that inspires the church to lead and participate in community service.